Vibrational and structural study of onopordopicrin based on the FTIR spectrum and DFT calculations - Chain, Fernando Ezequiel (2015)
In the present work, the structural and vibrational properties of the sesquiterpene lactone onopordopicrin (OP) were studied by using infrared spectroscopy and density functional theory (DFT) calculations together with the 6-31G∗ basis set. The harmonic vibrational wavenumbers for the optimized geometry were calculated at the same level of theory. The complete assignment of the observed bands in the infrared spectrum was performed by combining the DFT calculations with Pulay’s scaled quantum mechanical force field (SQMFF) methodology. The comparison between the theoretical and experimental infrared spectrum demonstrated good agreement. Then, the results were used to predict the Raman spectrum. Additionally, the structural properties of OP, such as atomic charges, bond orders, molecular electrostatic potentials, characteristics of electronic delocalization and topological properties of the electronic charge density were evaluated by natural bond orbital (NBO), atoms in molecules (AIM) and frontier orbitals studies. The calculated energy band gap and the chemical potential (μ), electronegativity (χ), global hardness (η), global softness (S) and global electrophilicity index (ω) descriptors predicted for OP low reactivity, higher stability and lower electrophilicity index as compared with the sesquiterpene lactone cnicin containing similar rings.